Cybersecurity, Technology, and Society: Developing an Interdisciplinary, Open, General Education Cybersecurity Course - He, Wu (2021)
This paper describes an interdisciplinary effort involving faculty from five different disciplines who came together to develop an interdisciplinary, open, general education cybersecurity course. The course, Cybersecurity, Technology, and Society, brings together ideas from interdisciplinary studies, information technology, engineering, business, computer science, criminal justice, and philosophy to provide students an interdisciplinary introduction to cybersecurity. We provide an overview of the rationale for the course, the process the authors went through developing the course, a summary of the course modules, details about the open education resources used as readings, and the types of assignments included in the class. We conclude by offering recommendations for others developing similar courses